PENGGUNAAN ELT WEBSITE UNTUK MENINGKATKAN KOMPETENSI GURU-GURU SMP DALAM KETRAMPILAN MENYIMAK - Hermariyanti Kusumadewi (Universitas Nasional, 2017)
Listening is an activity in which we can not only understand oral speech, but we can also respond to that utterance. The purpose of this study is to find out whether the use of ELT Web can improve the competence of junior high school teachers in listening skill and further with this paper can provide variation to teach listening by using technology. The method used from this research is quantitative method. The sample in this research is junior high school teachers. The researcher gave the question of pre-test in multiple choice, and listening post-test after practice using ELT Website. The results of this study indicate an increase in listening skills as indicated by the increase in post-test values.